Algebraic Thinking Ability Viewed From Students’ Interest Learning In Cooperative Integrated Reading and Composition (Circ) With Realistic Approach (Jurusan Matematika FMIPA UNNES, 2020)
The purpose of this study was to determine the algebraic thinking ability viewed from students’ interest learning in Cooperative Integrated Reading and Composition (CIRC) with realistic approach. The method used in this study was a quantitative method with the Posttest Only Control Design. The population was class X1 students in one of Senior High School in Pati academic year 2018/2019. Technique of sampling by using cluster random sampling, obtained XI MIPA 5 class as the experimental class and XI MIPA 6 class as the control class. The technique of collecting data used tests, questionnaires, and interviews. The data was analyzed by using proportion test and t-test. The results showed that (1) the algebraic thinking ability of students who get CIRC learning with a realistic approach achieved classical learning completeness, (2) the algebraic thinking ability of students who get CIRC learning models with realistic approach were better than algebraic thinking ability of students who get Discovery Learning, (3) students with upper interest learning tend to be able to fulfill generalization, transformational, and global meta-level activities, students with middle interest learning tend to be able to perform generational and transformational activities, but still tend difficult in conducting level-meta global activities, students with lower interest in learning tend to be able to do generational activities, but still tend difficult in carrying out transformational activities and level-meta global.